2000
DOI: 10.1128/jb.182.10.2838-2844.2000
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of α-Ketoglutarate by a sucA Mutant of Bradyrhizobium japonicum : Evidence for an Alternative Tricarboxylic Acid Cycle

Abstract: A complete tricarboxylic acid (TCA) cycle is generally considered necessary for energy production from the dicarboxylic acid substrates malate, succinate, and fumarate. However, a Bradyrhizobium japonicum sucA mutant that is missing ␣-ketoglutarate dehydrogenase is able to grow on malate as its sole source of carbon. This mutant also fixes nitrogen in symbiosis with soybean, where dicarboxylic acids are its principal carbon substrate. Using a flow chamber system to make direct measurements of oxygen consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 26 publications
1
49
1
Order By: Relevance
“…To our knowledge, throughout species, only three Kgd activities have been reported: in Euglena gracilis (34), in B. japonicum (17) and in association with a bifunctional protein cloned from E. coli, MenD (35). The activities in Euglena gracilis and the sucA mutant strain of B. japonicum have not been ascribed to specific genes or proteins, so it is not possible to tell whether the enzymes involved are homologs of Mtb's Kgd.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, throughout species, only three Kgd activities have been reported: in Euglena gracilis (34), in B. japonicum (17) and in association with a bifunctional protein cloned from E. coli, MenD (35). The activities in Euglena gracilis and the sucA mutant strain of B. japonicum have not been ascribed to specific genes or proteins, so it is not possible to tell whether the enzymes involved are homologs of Mtb's Kgd.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to detect high levels of glutamate dehydrogenase activity in M. smegmatis but not in Mtb or M. bovis bacillus Calmette-Guérin (data not shown). In Euglena gracilis (34) and rhizobia such as sucA B. japonicum, Mesorhizobium loti, and Rhizobium leguminosarum, it was suggested that the bypass pathway from ␣-ketoglutarate to succinate via SSA represents an adaptation to microaerophilic conditions inside legume nodules (17). Similarly the Kgd-GabD1 bypass pathway in Mtb may help the pathogen cope with conditions in host cells that are genuinely hypoxic, or, as appears to be the case in Mtb residing in macrophages in vitro, misperceived as hypoxic, perhaps because Mtb's oxygen-sensing mechanisms have been damaged by host-derived nitric oxide (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to interference from the crude cell extracts at 240 nm, the formation of fumarate was monitored by following the increase in absorbance at 300 nm. 2-Oxoglutarate dehydrogenase assay was performed by monitoring the release of 14 CO 2 from [1-14 C]2-oxoglutarate in the presence of NAD + and Coenzyme A (Green et al, 2000). For all assays, a milliunit (mU) of activity is defined as 1 nmol substrate reacted min 21 .…”
Section: Methodsmentioning
confidence: 99%
“…The resulting acetyl-CoA enters a modified citric acid cycle, which entails a shunt via succinate semialdehyde as in the ␣-proteobacterium Bradyrhizobium (18), circumventing the step catalyzed by ␣-ketoglutarate dehydrogenase. Under anaerobic conditions, pyruvate:NADPϩ oxidoreductase constitutes the key enzyme for a unique wax ester fermentation.…”
mentioning
confidence: 99%